THE IMPACT OF GREENWASHING ON FIRM VALUE DURING THE PERIOD BEFORE AND DURING THE COVID-19 CRISIS IN INDONESIA - Freshtriana, Freshtriana; Kim, Sung Suk (Ultimaccounting Jurnal Ilmu Akuntansi, 2025)
Abstract - This study examines the effect of greenwashing on firm valuation in Indonesia using panel data from 2018 to 2022. The research aims to determine whether greenwashing negatively impacts firm value, particularly during times of crisis. The results indicate a significant negative relationship between greenwashing practices and firm value, especially during crisis periods such as the COVID-19 pandemic. These findings underscore the importance of transparency in sustainability reporting and suggest that investors are becoming more critical of greenwashing claims. This study contributes to the growing body of literature on corporate sustainability and greenwashing, offering valuable insights into how misleading environmental claims can affect firm performance. It also has important implications for policymakers, investors, and companies in encouraging genuine sustainability efforts. Firms are urged to adopt authentic and verifiable sustainability practices, as failure to do so may erode investor trust and firm value. Overall, the study emphasizes the risks associated with deceptive sustainability reporting in a more environmentally conscious market. Keywords: Greenwashing; Firm Value; Crisis; ESG; Statistical Analysis